Współczesna duchowość chrześcijańska w Polsce. Opis, próba oceny, perspektywy - Sawa, Przemysław (Studia Pastoralne, 2026)
Today’s times exhibit the important transformations in Polish christianity. It’s easy to see a leaving from the faith transmitted by the tradition and customs (folk faith). It’s not always the change in direction the faith chosen and consciously experienced. Some catholics do not practise the faith, limiting it to external rites which have more to do with a culture than a real faith (rites Christmas or Easter). It’s true a lof of catholics or other christians (orthodox, lutherans, reformed) limit their faith to piety’s rites without the connecting with their life (their faith is Sunday service only). In the Catholic Church you may have noticed two trends. First there are misusages in folk piety, many a time deformed theologically. Second trend, ever more increasing in Poland and other Catholic countries, it’s the charismatic and evangelistic renewal of the Church, often connected with pentecostal experiences. It is associated with the charismatic awakening in the Catholic Church after the Second Vatican Council and it fits to the evangelical model of the renewal of the Church and the Papal call to the new evangelization. New times bring new practices which more than once are more expected and popular than traditional devotions in churches (the rosary, the service in first Tuesday and passion devotions). You can indicate the following pastoral activities: evangelizations, meetings with prayer for healing, worship concerts, charismatic prayers. At the same time you can noted a increased interest in Bible, a reading the word of God everyday and the necessity personal declaration Jesus as the Saviour and the Lord. This new religious culture converts an image of the Church, religion, faith. The Church becomes nearer to apostolic community. Those spiritual phenomena and practices insist on an appropriate theological, sociological evaluation and quite often psychological too. Anyways this charismatic and evangelistic spirituality contributes to the creating of the conscious and deeper implemented faith.